PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI PEMANFAATAN PRODUK TABUNGAN DAN PEMBIAYAAN SYARIAH KEPADA IBU-IBU PKK PERUMAHAN GRIYA BINA WIDYA UNRI KOTA PEKANBARU - Ficha Melina; Nurul Muyasaroh; Marina Zulfa; Rahmawati Nur; Aulia Fitri Sya’bani (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2026)
This Community Service Activity (PKM) aims to increase public understanding of Islamic banking and encourage the use of Islamic financial products in supporting family economic welfare. The activity was carried out in Tuah Madani Village with the main target of PKK women. The methods used include socialization related to the basic concepts of Islamic banking, savings products, financing, and Islamic investments such as gold savings. The results of the activity showed an increase in participants' understanding of the principles and products of Islamic banking. However, based on observations, several problems are still found, such as low sharia financial literacy and lack of public understanding of Sharia investment products. Nevertheless, this activity received a very positive response from the community, which was shown through the enthusiasm of the participants and the hope that similar activities could be carried out sustainably with more varied materials. Thus, this PKM activity contributes to increasing sharia financial literacy and opens up opportunities for community economic empowerment based on sharia principles.